British Cavalry on the Western Front 1916-1918 - Kenyon, D (Department of Defence Management and Security Analysis, 2008)
This thesis examines the activities and effectiveness of the British, Indian and Canadian cavalry which formed part of the British Expeditionary Force in France and Flanders (The ‘Western Front’) during the First World War. The study concentrates on the period from January 1916 to November 1918, focusing on four major Allied offensive battles; The Somme, July-November 1916 Arras, April 1917 Cambrai, November-December 1917 Amiens and the ‘100 Days’, August-November 1918 Other episodes of cavalry fighting associated with these offensives are also considered. It is argued in this study that the contribution of cavalry to the fighting on the Western Front has been consistently underestimated by historians, a trend which began with the Official History of the conflict and continues in even the most modern scholarship. The arm has been characterised as vulnerable to modern weapons, out of date, of little use in combat, and an unnecessary burden on scarce resources. Through analysis of the performance of mounted units in these battles, using data principally obtained from the unit War Diaries, as well as other primary sources, it is argued that cavalry were both much more heavily involved in fighting on the Western Front, and more effective, than has previously been acknowledged. The problems which constrained the performance of the cavalry are also exa mined. These included the limited understanding of their potential among senior officers, as well as command and control problems at lower levels. Issues concerning tactics, equipment, and interaction with other arms, (in particular tanks) are also examined. The evolution of the cavalry arm is also considered in the context of the evolution of the B.E.F. as a whole, and its part in the changing face of the conflict is examined, both as an agent of change, and as a beneficiary of wider developments in how the war was fought.